Pengaruh Struktur Kepemilikan Saham dan Struktur Dewan Komisaris terhadap Kinerja Perusahaan - Martono, Cyrillius; Sina, Siprianus Salvatore (Jurnal Akuntansi Kontemporer, 2011)
Shareholding structure and the structure of the board of commissioners that are the focus in this study were (1) the internal ownership structure (insider ownership), which share ownership by managers and commissioners, (2) stock ownership by blockholders, ie individuals and or institutions that own shares company by 5% or more, (3) the proportion of independent commissioners (outside board), and (4) the size of the board of commissioners (board size). In determining the structure of share ownership and the board structure as the application of corporate governance mechanisms, firms are always faced with the question of costs (cost) and benefits (benefits). As a result, the company could substitute the level of use of the mechanism of the shareholding structure and board structure of the board of commissioner such a way to balance the marginal cost and marginal benefit. Hence the hypothesis proposed in this research are: (l) the company doing the substitution between ownership structure and the structure of the board, (2) ownership structure and the board structure significantly influence the performance of the company. Companies that were sampled in this research is a registered company in Indonesia Stock Exchange in 2008. Based on purposive sampling acquired 100 companies are used as a sample. Testing the first hypothesis is done by using two stages least squared while the second hypothesis testing is done using ordinary least squared. The results of testing the first hypothesis suggests that companies in Indonesia has yet to substitute between ownership structure and the structure of the board of commissioners. Except found that internal ownership but also turns positive effect on the proportion of independent commissioners. The second hypothesis as not entirely proven. However, it was found that the presence of blockholders apparently significant effect on company performance. Researchers then expected to find a proxy or a variable and more precise control for the study still found a model that does not fit. Keywords: board size, blockholders, insider ownership, outside shareholders.